New Zealand, new futures, new ways of science engaging with society? - Frame, Bob; Collins, Alison; Gordon, Richard (New Zealand Science Review, 2011)
​Science and innovation are largely valued in New Zealand as drivers of economic growth. Yet society, in charting growth, is facing increasingly real resource limits and impacts threatening the integrity of life-supporting aspects of our environment. Through a deeper understanding of what we mean by science and society, New Zealand has the potential to be truly innovative, both locally and internationally, around complex issues such as sustainable use of natural resources and reducing the use of damaging materials and processes, while keeping growth firmly on the agenda. In this paper we argue that, though gains could be made through a changed science agenda, the most significant step-change could occur at the interface between science and society – particularly in the way science engages, motivates, and drives the future.